2021
DOI: 10.1109/access.2021.3062875
|View full text |Cite
|
Sign up to set email alerts
|

Investigating COVID-19 News Across Four Nations: A Topic Modeling and Sentiment Analysis Approach

Abstract: Newspapers are very important for a society as they inform citizens about the events around them and how they can impact their life. Their importance becomes more crucial and indispensable in the times of health crisis such as the current COVID-19 pandemic. Since the starting of this pandemic newspapers are providing rich information to the public about various issues such as the discovery of a new strain of coronavirus, lockdown and other restrictions, government policies, and information related to the vacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(73 citation statements)
references
References 26 publications
(29 reference statements)
2
56
0
2
Order By: Relevance
“…As for South Korea, with 10,076 articles and 127 topics, the country's top five topics were economic relief, geopolitics, impact on retail, lower GDP and COVID-19 cases. To conclude, topic modeling revealed common themes to be education, economy, US and sports across four nations and the sentiment analysis indicated that the UK had 73.23% of news being negative, in contrast to South Korea's 54.47% being positive [19]. Fourth, based on media framework theory, the study of Thirumaran et al [23] focused on newspapers from Singapore and New Zealand and investigated the relationship between destination crisis management strategy and the effects of news portrayal out of traveling concerns.…”
Section: Sentiment Analysis and Text Mining With Social And News Mediamentioning
confidence: 97%
See 1 more Smart Citation
“…As for South Korea, with 10,076 articles and 127 topics, the country's top five topics were economic relief, geopolitics, impact on retail, lower GDP and COVID-19 cases. To conclude, topic modeling revealed common themes to be education, economy, US and sports across four nations and the sentiment analysis indicated that the UK had 73.23% of news being negative, in contrast to South Korea's 54.47% being positive [19]. Fourth, based on media framework theory, the study of Thirumaran et al [23] focused on newspapers from Singapore and New Zealand and investigated the relationship between destination crisis management strategy and the effects of news portrayal out of traveling concerns.…”
Section: Sentiment Analysis and Text Mining With Social And News Mediamentioning
confidence: 97%
“…Most COVID-19-related sentiment analysis and text mining studies have analyzed social media data, while few comparative studies have suggested that the topic coverage of social media is narrower, i.e., the sentiment is more likely to be negative and has a shorter life span than that of news media [17,18]. By contrast, news articles that are written by journalists and subject matter experts present facts that make them more objective [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies combined both topic modeling and sentiment analysis to assess people's sentiments on multiple aspects of the pandemic. In [17], the authors investigated COVID-19 related news across four countries using Top2vec for topic modeling and RoBERTa for sentiment analysis. In [18], the authors used multiple topic modeling techniques and sentiment analysis algorithms to analyze content from Brazil and USA based twitter accounts.…”
Section: Related Workmentioning
confidence: 99%
“…Also, a study done by Saif Hassan, Fernández Miriam, He Yulan and Alani Harith [15] provided a comprehensive overview of "On Stop-words, Filtering and Data Sparsity for Sentiment Analysis of Twitter" in 2014. Many such works are done by the researchers in [16][17][18][19][20][21][22][23][24][25][26][27]. Above research works are based on sentiment analysis using different methods on social media data in different domains.…”
Section: Related Workmentioning
confidence: 99%
“…The tweets are classi ed into 3 polarity; positive, negative, neutral sentiment. Our model consists of results from 3 types of Machine Learning models [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]; Decision Tree, SVM, and Logistic Regression. The simulation is performed better under this environment with 88.67% accuracy in SVM.…”
Section: Trainingmentioning
confidence: 99%